FEATURES OF FAT AND CARBOHYDRATE METABOLISM IN PREGNANT WOMEN WITH PATHOLOGICAL GESTATIONAL WEIGHT GAIN (E Conference Zone, 2022)
the article discusses the features of body weight increase in the dynamics of the gestational process in women with different initial anthropometric indicators.